The Cognition Hypothesis: A Synthesis and Meta‐Analysis of Research on Second Language Task Complexity. Issue 2 (5th April 2013) - Jackson, Daniel O.; Suethanapornkul, Sakol
Abstract : This study employed synthetic and meta‐analytic techniques to review the literature on the Cognition Hypothesis, which predicts that increasing task complexity influences the quality of second language production. Based on 8 inclusion criteria, 17 published studies were synthesized according to key features. A subset of these studies ( k = 9) was also meta‐analyzed to investigate the overall effects of raising resource‐directing task demands on learner output during monologic tasks. The synthesis of 17 primary studies revealed an assortment of treatments and measures. Among the 9 comparable studies, the meta‐analysis uncovered small positive effects for accuracy and small negative effects for fluency. This lends support to the Cognition Hypothesis; however, the present study also disconfirms predictions regarding syntactic complexity. Implications for research and pedagogy are discussed.